Association between El Niño and extreme temperatures in southern South America in CMIP5 models. Part 1: model evaluation in the present climate - Collazo, Soledad Maribel (2021)
Climate variability might temporarily improve or mitigate the effects of increasingglobal warming. Understanding and estimating internal variability is just as important as understandingthe role of anthropogenic forcing, as the combination of both drives climate events in thereal world. The objective of this work is to analyze the relationship between the SST of the equatorialPacific and 4 extreme temperature indices in southern South America considering griddedobservational data (HadEX3), reanalyses (ERA-Interim, NCEP1, NCEP2), and global climatemodels participating in the Coupled Model Intercomparison Project Phase 5 (CMIP5) in the historicalperiod 1979−2005. For this, correlations and quantile regression for the 90th percentilewere estimated between the variables. Moreover, to assess the performance of the reanalysis andCMIP5 models, multiple metrics were calculated. The observations showed that warm conditionsin the equatorial Pacific are mainly associated with a higher occurrence of warm nights in thenorth and center of Argentina and Chile in winter and spring. However, the different reanalysesconsidered in this study showed discrepancies in representing these relationships. Several CMIP5models were generally able to simulate correlation patterns for the warm extremes of the minimumand maximum temperature in comparison to HadEX3. These types of studies are critical tounderstanding whether climate models simulate temperature extremes in association with physicalprocesses, providing greater confidence in their future projections.